Search for squarks and gluinos in events with jets and missing transverse energy using 2.1 fb(-1) of p(p)over-bar collision data at root s=1.96 TeV - D phi Collaboration - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (Elsevier B.V., 2008)
A data sample corresponding to an integrated luminosity of 2.1 fb(-1) collected by the D phi detector at the Fermilab Tevatron Collider was analyzed to search for squarks and gluinos produced in p (p) over bar collisions at a center-of-mass energy of 1.96 TeV. No evidence for the production of such particles was observed in topologies involving jets and missing transverse energy, and 95% C.L. lower limits of 379 GeV and 308 GeV were set on the squark and gluino masses, respectively, within the framework of minimal supergravity with tan beta = 3, A(0) = 0, and mu < 0. The corresponding previous limits are improved by 54 GeV and 67 GeV. (c) 2008 Elsevier B.V. All rights reserved.